Evertor Muscle Function as a Predictor of Recurrence of Deformity Following Treatment of Pediatric Idiopathic Clubfoot, A Cohort Study - Lewsirirat, Supphamard; Klongkaew, Phatchaya; Piyapromdee, Urawit (ASEAN Journal of Rehabilitation Medicine, 2023)
Objectives: This study aimed to evaluate the relationship between evertor muscle function and the recurrence of deformity following treatment of pediatric idiopathic clubfoot. Study design: A cohort study. Setting: Maharat Nakhon Ratchasima hospital, Nakhon Ratcha-sima province, Thailand. Subjects: Sixty-two children with idiopathic clubfoot. Methods: Children with idiopathic clubfoot who were treated and followed up at Maharat Nakhon Ratchasima hospital, Thailand for a minimum of 2 years were enrolled. After the initial success of serial manipulation and plaster casting, parents were advised regarding the child’s foot evertor muscle training and Achilles and tibialis posterior tendon stretching exercises without using the Denis Browne bar. Demographic data included age at onset, gender, Dimeglio score, number of casts required for initial correction, the need for Achilles tenotomy, and evertor muscle grading before and after training. All children were evaluated regularly for signs of recurrence. Univariate analysis was used to analyze the relative risk of recurrence with good and poor evertor muscle function. Results: Sixty-two children with clubfoot, 42 males (67.7%) and 20 females (32.3%) were enrolled. Twenty-six (41.9%) children had bilateral deformities. Recurrence of deformities after treatment was documented in 22 children (35.5%). Severe deformity at presentation according to the Dimeglio score was a significant predictor of recurrence (p 0.012). After adjusting for relative risk base on the Dimeglio score, the recurrence was significantly higher in the poor evertor muscle function group with an adjusted RR of 9.59 (95%CI 3.43 - 26.80). Conclusions: Evertor muscle function is associated with the recurrence rate of pediatric idiopathic clubfoot.